INTRODUCTION OF DIGITAL TELEVISION OF DVB-T2 ON THE 9 CHANNEL IN THE DNIPRO CITY - Krasovska, Y. O.; Magro, V. I. (Radio Electronics, Computer Science, Control, 2017)
Context. The problem of the regional television channel transition from analogue broadcasting to digital broadcasting has been solved. Objective is to identify and overcome the difficulties of the local transition to digital television standard DVB-T2 on the example of the usual regional television company. Method. A two-level transition of the regional TV channel from analog to digital broadcasting is proposed. The first level includes the election of the best video format for broadcasting in the DVB-T2 standard and HDTV, as well as two options for replacing the television equipment that can provide digital terrestrial second generation digital terrestrial television and high definition television. The two options for replacing equipment are due to the limited funds that can allocate TV company for a short time interval on the technical re-equipment. At the second level, the city level to calculate the real range of coverage of digital broadcasting and the proposed methods of achieving it. Results. In this example, the technique of the transition from analogue to digital broadcasting for usual regional television companies is shown. Calculations carried out on the example of TV Private TV Dnipro – «Channel 9», the city Dnipro showed that the existing analogue system fixing, processing and transportation of the video on the regional TV channel will require the complete replacement of the equipment. Depending on the volume of finances allocated for modernization, two ways of replacing equipment are suggested. Calculations showed that minimally satisfactory coverage of digital TV in the city Dnipro provided at a distance of about 65 km. However, the quality of digital television on the verge of coverage is not provided in full by poor field strength at the point of maximum distance from the TV center. Conclusions. The method of transition of the regional TV channel from analogue broadcasting to digital broadcasting has been developed. It can be recommended for use in practice, considering local conditions in other regional channels in Ukraine.